Mobile device: centralized local area network-based classroom management system - Bathan, Mark Angelo Sandoval; Paculaba, Anna Monica Cruz (Penerbit Universiti Kebangsaan Malaysia, 2023)
With the advancement of technology nowadays, the emergence of mobile phones in a classroom set – up has been at a premium in delivering quality education. This study aimed to determine the current electronic learning platforms used by the faculty and develop a mobile and local Wi-Fi-based classroom management system for Samar State University that illustrates how a mobile phone can serve as an instrument in the advancement of classroom management. The incremental Model was used as a method in the development of the system. The result revealed that the developed system contains features that are not present in the existing system used by the faculty which bridged the gap between the online classroom and traditional classroom setting.